2016
DOI: 10.1021/acsami.5b12212
|View full text |Cite
|
Sign up to set email alerts
|

Kartogenin-Incorporated Thermogel Supports Stem Cells for Significant Cartilage Regeneration

Abstract: Recently, cartilage tissue engineering (CTE) attracts increasing attention in cartilage defect repair. In this work, kartogenin (KGN), an emerging chondroinductive nonprotein small molecule, was incorporated into a thermogel of poly(L-lactide-co-glycolide)-poly(ethylene glycol)-poly(L-lactide-co-glycolide) (PLGA-PEG-PLGA) to fabricate an appropriate microenvironment of bone marrow mesenchymal stem cells (BMSCs) for effective cartilage regeneration. More integrative and smoother repaired articular surface, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
143
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 46 publications
3
143
0
Order By: Relevance
“…Gel/KGN/BMSC implantation produced better histological cartilage repairs and mechanical properties, and greater extracellular matrix deposition than the implantation of thermogel only or BMSC‐loaded thermogel. Furthermore, more integrated and smoother repaired articular surfaces, more abundant characteristic glycosaminoglycans (GAGs) and Col II, and less degeneration of normal cartilage were observed in the KGN/BMSCs co‐loaded thermogel group in vivo . Shi et al devised a photo‐cross‐linked scaffold using KGN‐encapsulated nanoparticles integrated into an ultraviolet‐reactive, rapidly cross‐linkable scaffold for cartilage regeneration.…”
Section: Kgn and The Promotion Of Cartilage Healingmentioning
confidence: 99%
See 3 more Smart Citations
“…Gel/KGN/BMSC implantation produced better histological cartilage repairs and mechanical properties, and greater extracellular matrix deposition than the implantation of thermogel only or BMSC‐loaded thermogel. Furthermore, more integrated and smoother repaired articular surfaces, more abundant characteristic glycosaminoglycans (GAGs) and Col II, and less degeneration of normal cartilage were observed in the KGN/BMSCs co‐loaded thermogel group in vivo . Shi et al devised a photo‐cross‐linked scaffold using KGN‐encapsulated nanoparticles integrated into an ultraviolet‐reactive, rapidly cross‐linkable scaffold for cartilage regeneration.…”
Section: Kgn and The Promotion Of Cartilage Healingmentioning
confidence: 99%
“…Furthermore, more integrated and smoother repaired articular surfaces, more abundant characteristic glycosaminoglycans (GAGs) and Col II, and less degeneration of normal cartilage were observed in the KGN/BMSCs co-loaded thermogel group in vivo. 7 can release kartogenin to 25 mM over 3 weeks in 100 mL PBS were injected into the knee joint at weeks 6 and 9 after OA induction. Normal articular cartilage from rats that did not undergo surgical procedures is also shown.…”
Section: Kgn and The Promotion Of Cartilage Healingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have found that kartogenin (KGN), a small compound can promote the chondrogenic differentiation of human and mouse mesenchymal stem cells (MSCs) [13]. Several studies have used KGN to enhance wounded cartilage regeneration [14, 15]. We have shown that KGN-treated autologous tendon graft can enhance the wounded rat meniscus healing [16].…”
Section: Introductionmentioning
confidence: 99%